Assistance for business startups processing Etawa goat's milk to maximize local potential in Purworejo - Titin Ekowati; Fithri Rahmawati; Esti Margiyanti Utami (Universitas Muhammadiyah Magelang, 2022)
This community service program is carried out to help startup business actors. Beginner business actors are expected to be able to develop businesses that have been initiated with their groups. The purpose of this community service program is to offer business support to start-up business groups that produce